Advanced infant HIV infection with Cytomegalovirus coinfection following interruption of maternal antiretroviral therapy: a case report - Prisillia Brigitta; Adinda Paramitha Sukma Damayanti; Delicia Rudy; I Putu Oka Kresna Jayadi (Pediatric Sciences Journal, 2026)
Background: Despite major global progress in the prevention of mother-to-child transmission (PMTCT), vertical HIV transmission continues to occur, particularly in settings where continuity of maternal care and viral suppression are not maintained. Infants infected perinatally remain at high risk for rapid disease progression, severe immunosuppression, and early mortality, especially in the absence of timely diagnosis and antiretroviral therapy (ART). Coinfections such as cytomegalovirus (CMV) may further complicate the clinical course and influence management decisions. Case Presentation: We report a case of a 7-week-old female infant presenting with chronic diarrhea, fever, severe malnutrition, jaundice, and pancytopenia. The infant was born at term via elective cesarean section to a mother with known HIV infection who had discontinued ART prior to and during pregnancy. Neonatal prophylaxis consisted of zidovudine monotherapy based on reported maternal adherence. Early Infant Diagnosis confirmed HIV-1 infection with profound immunosuppression (CD4 37 cells/µL, 2.6%) and a high viral load (2.99 ×10⁶ copies/mL). Further evaluation revealed active CMV infection with significant hepatobiliary involvement. Management included supportive stabilization, treatment of CMV infection, opportunistic infection prophylaxis, and carefully timed ART initiation in the context of severe hepatic dysfunction and risk of immune reconstitution inflammatory syndrome. Conclusion: This case highlights how disruption along the PMTCT cascade, including interruption of maternal ART and misclassification of neonatal transmission risk, can lead to advanced HIV disease in early infancy despite obstetric preventive measures. Sustained maternal viral suppression, accurate perinatal risk assessment, and timely initiation of ART remain critical to preventing severe pediatrics HIV.